2003
DOI: 10.1172/jci200318104
|View full text |Cite
|
Sign up to set email alerts
|

Increased T cell reactivity to amyloid β protein in older humans and patients with Alzheimer disease

Abstract: Alzheimer disease (AD) is characterized by the progressive deposition of the 42-residue amyloid beta protein (Abeta) in brain regions serving memory and cognition. In animal models of AD, immunization with Abeta results in the clearance of Abeta deposits from the brain. However, a trial of vaccination with synthetic human Abeta1-42 in AD resulted in the development of meningoencephalitis in some patients. We measured cellular immune responses to Abeta in middle-aged and elderly healthy subjects and in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
128
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 287 publications
(134 citation statements)
references
References 66 publications
3
128
1
2
Order By: Relevance
“…A major question that arises regarding the antibodyindependent strategy we have described is whether the induction of an inflammatory response in the brains of humans that includes a Th1 component will have untoward side effects (50)(51)(52). It is postulated that the meningoencephalitis observed following Aβ immunization was related to the induction of Aβ-reactive T cells, and we have shown that there is increased T cell reactivity to Aβ in elderly individuals (53). In our animal studies, in which we induced EAE or nasally administered GA+IVX-908, we did not observe induction of anti-Aβ antibodies or priming of anti-Aβ T cells, though the latter remains a possibility.…”
Section: Figurementioning
confidence: 84%
“…A major question that arises regarding the antibodyindependent strategy we have described is whether the induction of an inflammatory response in the brains of humans that includes a Th1 component will have untoward side effects (50)(51)(52). It is postulated that the meningoencephalitis observed following Aβ immunization was related to the induction of Aβ-reactive T cells, and we have shown that there is increased T cell reactivity to Aβ in elderly individuals (53). In our animal studies, in which we induced EAE or nasally administered GA+IVX-908, we did not observe induction of anti-Aβ antibodies or priming of anti-Aβ T cells, though the latter remains a possibility.…”
Section: Figurementioning
confidence: 84%
“…In our study, almost all SDPM1-specific antibodies induced in young or old APPswePSEN1(A246A) transgenic mice were of the IgG1 subtype; The 10:1 ratio of IgG1 to IgG2a in these experiments is reflective of a Th2 type response, as Th1 responses typically induce IgG2a antibodies while Th2 responses typically induce IgG1 (or IgG2b)(Finkelman et al, 1990). Because the T cell epitopes in Aβ 1–40/1–42 are present in the C-terminal half of the peptide and are absent in the N-terminal 15 amino acids(Monsonego et al, 2001; Monsonego et al, 2003), a number of strategies aimed at using only the N-terminal half of Aβ peptide are currently being investigated to minimize Th1 T cell responses. Immunization with Aβ 1–5 multimers (conjugated with ovalbumin T cell epitope (OVAT)(Bard et al, 2003) or with murine leukemia virus particles and PDGF protein(Bach et al, 2009)), with Aβ 1–15 multimers (conjugated with pan HLA DR-binding peptide (PADRE) and Alum(Agadjanyan et al, 2005), delivered in liposomes(Muhs et al, 2007), or delivered intranasally(Maier et al, 2006)), or with Aβ 1–28 multimers (conjugated to Mannan(Ghochikyan et al, 2006b)) all produced minimal Th1 responses while reducing Aβ plaque burden.…”
Section: Discussionmentioning
confidence: 99%
“…These have focused on passive immunization, where therapeutic antibodies are directly administered(Bard et al, 2003; Hock et al, 2003; Lee et al, 2006; Pan et al, 2002; Tucker et al, 2008; Yamada et al, 2009), as well as modified active Aβ amyloid immunization strategies(Ghochikyan et al, 2006a; Ghochikyan et al, 2006b; Lemere, 2009; Lemere et al, 2007; Moretto et al, 2007; Schneeberger et al, 2009; Seabrook et al, 2007; Sigurdsson et al, 2004). Many of these latter approaches involve using shortened N-terminal fragments of the Aβ 1–42 peptide that lack the predominant T cell epitopes (which occur in the more C-terminal region of Aβ 1–42 )(Kutzler et al, 2006; Monsonego et al, 2001; Monsonego et al, 2003). While such a modified active immunization approach is logical, vaccination using shortened Aβ peptides may also preclude the development of therapeutic humoral responses against certain quaternary Aβ amyloid forms, which may not be present in such immunogens.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been reported that AD patients have T cells with shorter telomeres, and telomere length significantly correlated with AD severity [78]. AD patients have increased T cell reactivity to Aβ [79, 80], and the phenotype of the T cells in circulation is shifted, with increased CD4 + IFN-γ + and CD8 + IFN-γ + T cells observed [81, 82]. Saresella and colleagues also reported an Aβ-specific population of Th17 and Th9 cells that was increased in AD patients in comparison to healthy control subjects [75].…”
Section: Reviewmentioning
confidence: 99%